2019
DOI: 10.1021/acs.joc.8b02899
|View full text |Cite
|
Sign up to set email alerts
|

Ru-Catalyzed Selective C–H Bond Hydroxylation of Cyclic Imides

Abstract: We report on cyclic imides as weak directing groups for selective mono-hydroxylation reactions using ruthenium catalysis. Whereas acyclic amides are known to promote the hydroxylation of the C(sp 2)-H bond enabling 5-membered ring ruthenacycle intermediates, the cyclic imides studied herein enabled the hydroxylation of the C(sp 2)-H bond via a larger 6-membered ruthenacycle intermediates. Furthermore, mono-hydroxylated products were exclusively obtained (even in the presence of over-stoichiometric amounts of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Polyaromatic substrates 26-28c were also shown to be highly reactive. As a prominent structural motif, N-arylpyrrolidinones have been used in Ru(II)-catalysed C-H hydroxylation 56,57 . We found that the boron-mediated directed C-H hydroxylation of N-phenylpyrrolidinone (29a) in the presence of BBr 3 could provide the desired product 29c with a 79% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Polyaromatic substrates 26-28c were also shown to be highly reactive. As a prominent structural motif, N-arylpyrrolidinones have been used in Ru(II)-catalysed C-H hydroxylation 56,57 . We found that the boron-mediated directed C-H hydroxylation of N-phenylpyrrolidinone (29a) in the presence of BBr 3 could provide the desired product 29c with a 79% yield.…”
Section: Resultsmentioning
confidence: 99%
“…of (NH 4 ) 2 S 2 O 8 in (3:1) TFA/TFAA at 80 0 C successfully removed the ortho-proton of N-phenyl phthalimides for selective hydroxylation (Scheme 41). [55] The reaction proceeds via the formation of favorable six membered ruthenacycle (activat- Based on their previous work, [30] Singh et. al.…”
Section: Tfa Mediated Hydroxylationmentioning
confidence: 99%
“…of (NH 4 ) 2 S 2 O 8 in (3:1) TFA/TFAA at 80 0 C successfully removed the ortho ‐proton of N ‐phenyl phthalimides for selective hydroxylation (Scheme 41). [55] The reaction proceeds via the formation of favorable six membered ruthenacycle (activating H a ) rather than five membered (with H b ) cyclic intermediate for selective hydroxylation of C−H bond. A large number of imides with diverse functional groups like Me, NEt 2 , F, Cl, NO 2 , CO 2 Et etc.…”
Section: Tfa− From Tfa and Phi(otfa)2 As Hydroxylating Agentmentioning
confidence: 99%
“…Alternatively, N ‐arylphthalimide derivatives were found to be suitable partners to provide exclusively mono‐hydroxylated products with anilide site‐selectivity regardless of the equivalents of oxidant being used (Scheme ) . The reactions, which were catalyzed by ruthenium or palladium catalysts, were tolerant to a broad scope of functional groups.…”
Section: C−o Bond Forming Reactionsmentioning
confidence: 99%